Distribution of Pruritus and Its Association With Serum Parathormone Level in Chronic Kidney Disease (Stage-5) Patients On Maintenance Hemodialysis - Hasan, Rafiqul; Chowdhury, Md Nizamuddin; Islam, Md Nazrul; Ahmed, Parvez Iftekher; Anwar, ASM Tanim; Hossain, Mohammad Bellal; Ali, Mohammad Shawkat; Rahman, Md Saidur (Journal of Dhaka Medical College, 2020)
Background: Pruritus is a common manifestation in patients on hemodialysis. The aim of this study is to determine the distribution of pruritus and evaluate the association between pruritus and serum parathormone levels in chronic kidney disease patients on maintenance haemodialysis. Methods:This analytic, descriptive, cross-sectional study was performed over 191 patients of maintenance haemodialysis in 2014. Information related to the patients including age, gender, residence, pruritus was extracted from questionnaires. Serum levels of intact parathormone were measured & data were analyzed. Results: 68% of the patients had pruritus. The Mean ± SD of serum parathormone was 53.25±7.96 pg/ml in patients with pruritus and 81.91±9.34 pg/ml in patients without pruritus. Our study showed that most patients with pruritus had normal serum parathormone levels and no significant association was found between pruritus and serum parathormone levels. Conclusion: serum parathormone level may not play a role in uraemic pruritus in these patients. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 54-59